2000
DOI: 10.1097/00005176-200010000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Is Lactobacillus GG Helpful in Children With Crohn’s Disease? Results of a Preliminary, Open-Label Study

Abstract: Findings in this pilot study show that Lactobacillus GG may improve gut barrier function and clinical status in children with mildly to moderately active, stable Crohn's disease. Randomized, double-blind, placebo-controlled trials are warranted for a final assessment of the efficacy of Lactobacillus GG in Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
194
0
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(205 citation statements)
references
References 27 publications
1
194
0
10
Order By: Relevance
“…18 Oral administration of LGG reduced the severity of Crohn's disease in children as judged by a reduction in PCDAI score. 19 In addition, it has been suggested that Lactobacillus exerts an anti-inflammatory effect in milk-hypersensitive children as a result of downregulation of the immunoinflammatory response. 20 The second aim of this pilot study was to test the hypothesis that the administration of probiotics reduces intestinal inflammation in CF.…”
Section: Introductionmentioning
confidence: 99%
“…18 Oral administration of LGG reduced the severity of Crohn's disease in children as judged by a reduction in PCDAI score. 19 In addition, it has been suggested that Lactobacillus exerts an anti-inflammatory effect in milk-hypersensitive children as a result of downregulation of the immunoinflammatory response. 20 The second aim of this pilot study was to test the hypothesis that the administration of probiotics reduces intestinal inflammation in CF.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Probiotics have already been used safely in intestinal bowel diseases 23 such as ulcerative colitis or in chronic pouchitis, 24 to decrease symptoms in patients with irritable bowel syndrome, 25 or even to improve the clinical status of children with stable Crohn's disease. 26 In addition, new recombinant strains of probiotics are used as novel therapeutic strategies to deliver vaccines 27 or biologically active compounds such as interleukin-10 in murine colitis. 28,29 Lactobacillus plantarum is a nonpathogenic, noninvasive, Gram-positive bacterium found in the normal mucosal flora of the human mouth and intestine and frequently associated with lactic acid fermented foods of plant origin.…”
mentioning
confidence: 99%
“…In the maintenance phase there was a non-significant trend towards decreased relapse rates in the E. coli group v. the placebo group. Gupta et al (2000) have examined the effects of LGG in four children with steroid refractory CD, two of whom were taking concomitant metronidazole. Colonisation with LGG and a sustained reduction in disease activity associated with improved intestinal permeability was demonstrated in all patients, suggesting a mechanism for the therapeutic effect.…”
Section: Probiotics and Prebiotics To Treat Activementioning
confidence: 99%